The Influence of Instagram Social Media Marketing @Aerostreet Through Brand Identity, Brand Image on Purchase Intention in Bandung Students - Raihan Daniel Dwi Febrian; Abdurrahman Faris Indriya Himawan (Green Publisher Indonesia, 2025)
This study aims to explore the impact of social media marketing through Instagram @Aerostreet on students' purchase intention in Bandung, considering the variables of brand identity, brand image, brand integrity, and brand interaction. The approach used in this research is quantitative, employing the Structural Equation Modeling (SEM-PLS) method. Data were collected through surveys targeting students in Bandung who follow or engage with the Instagram account @Aerostreet. The research findings indicate that brand identity and brand image have a positive and significant influence on purchase intention. Brand integrity and brand interaction contribute to increasing customer satisfaction, which indirectly affects students' purchase intention toward Aerostreet products. This study provides insights for local brands in optimizing strategi pemasaran digital through social media to enhance consumer trust and loyalty.